2015
DOI: 10.1002/cne.23744
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism and phenotypic plasticity in the antennal lobe of a stingless bee, Melipona scutellaris

Abstract: Among social insects, the stingless bees (Apidae, Meliponini), a mainly tropical group of highly eusocial bees, present an intriguing variety of well-described olfactory-dependent behaviors showing both caste- and sex-specific adaptations. By contrast, little is known about the neural structures underlying such behavioral richness or the olfactory detection and processing abilities of this insect group. This study therefore aimed to provide the first detailed description and comparison of the brains and primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 101 publications
(153 reference statements)
1
25
0
Order By: Relevance
“…To identify macroglomeruli a quantitative threshold that defines outliers according to 80% of the distribution of glomerular volumes was used: normalVoutlier> VnormalU+ k (normalVnormalU VnormalL), where V U is the upper percentile (90%) and V L the lower percentile (10%) of glomerular volume distribution. We used k = 3 as a conservative value that successfully categorized macroglomeruli in several hymenopteran species (Kuebler et al, ; Streinzer et al, ; Roselino et al, ). Thus, glomeruli whose volume was above this threshold were considered macroglomeruli.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify macroglomeruli a quantitative threshold that defines outliers according to 80% of the distribution of glomerular volumes was used: normalVoutlier> VnormalU+ k (normalVnormalU VnormalL), where V U is the upper percentile (90%) and V L the lower percentile (10%) of glomerular volume distribution. We used k = 3 as a conservative value that successfully categorized macroglomeruli in several hymenopteran species (Kuebler et al, ; Streinzer et al, ; Roselino et al, ). Thus, glomeruli whose volume was above this threshold were considered macroglomeruli.…”
Section: Methodsmentioning
confidence: 99%
“…Another striking example of such neuroanatomical and physiological adaptations is the existence of enlarged glomeruli, called macroglomeruli , dedicated to pheromone detection and processing (Burrows et al, ; Arnold et al, ; Hanson et al, ; Sandoz, ; Nishikawa et al, ; Nishino et al, ). In most cases, macroglomeruli are male dimorphic adaptations devoted to sex pheromone processing, but they have also been discovered in the females of some social Hymenoptera (Arnold et al, ; Kleineidam et al, ; Roselino et al, ). In leaf‐cutting ants, for instance, a macroglomerulus found only in large workers is thought to process trail pheromone information (Kelber et al, ; Kuebler et al, ).…”
mentioning
confidence: 99%
“…On average, E. dilemma females had 21 additional glomeruli relative to males. An increased number of glomeruli in females is commonly observed in bees, although the differential can vary substantially (103 vs. 160 in the honey bee [−36%]; 159 vs. 200 in the stingless bee Melipona scutellaris [−21%]; 98 vs. 133 in the long horned bee Eucera berlandi [−27%]; Roselino et al, ; Streinzer, Kelber, et al, ). Interestingly, the difference between sexes in E. dilemma was the lowest measured for any bee species so far (141 vs. 162, −13%), which may indicate that male and female orchid bees have more similar olfactory capabilities compared to other bee lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Where V G is the volume of the focal glomerulus, V L the 10th percentile, and V U the 90th percentile of glomerular volume distribution. Following Roselino, Hrncir, da Cruz Landim, Giurfa, and Sandoz (), glomeruli with a K value between 1.5 and 3 were defined as mild outliers and glomeruli with a K ≥ 3 were defined as extreme outliers. Only extreme outliers were classified as macroglomeruli.…”
Section: Methodsmentioning
confidence: 99%
“…Although sexually dimorphic structures have been found in the nervous system of non‐ Drosophila insects (Rössler et al , ; Rospars and Hildebrand, ; Berg et al , ; Nishikawa et al , ; El Jundi et al ., ; Mysore et al , ; Nishino et al , ; Baba etisoforms) were identified using al. , ; Nakanishi et al , ; Hu et al , ; Streinzer et al , ; Roselino et al , ; Zhao et al , ), the molecular, neuronal and developmental mechanisms underlying the sexual dimorphism of the brain are not well understood.…”
Section: Introductionmentioning
confidence: 99%